2021
DOI: 10.1073/pnas.2019554118
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell epigenome manipulation by synthetic histone acetylation catalyst system

Abstract: Chemical modifications of histones, such as lysine acetylation and ubiquitination, play pivotal roles in epigenetic regulation of gene expression. Methods to alter the epigenome thus hold promise as tools for elucidating epigenetic mechanisms and as therapeutics. However, an entirely chemical method to introduce histone modifications in living cells without genetic manipulation is unprecedented. Here, we developed a chemical catalyst, PEG-LANA-DSSMe 11, that binds with nucleosome’s acidic patch and promotes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…However, cellular deacetylases can act quickly on these sites resulting in deacetylation, a problem that most likely also applies to other types of acylations. Recently, Fujiwara et al (2021) demonstrated that site-specific acylations can also be introduced in vivo via a protease-resistant nucleosome-binding catalyst and a cellpermeable acetyl donor. Subsequent development of this exiting method might enable us to study the effects of histone acylations on nucleosome assembly in vivo.…”
Section: Impact Of Histone Acylations On Chromatin Structurementioning
confidence: 99%
“…However, cellular deacetylases can act quickly on these sites resulting in deacetylation, a problem that most likely also applies to other types of acylations. Recently, Fujiwara et al (2021) demonstrated that site-specific acylations can also be introduced in vivo via a protease-resistant nucleosome-binding catalyst and a cellpermeable acetyl donor. Subsequent development of this exiting method might enable us to study the effects of histone acylations on nucleosome assembly in vivo.…”
Section: Impact Of Histone Acylations On Chromatin Structurementioning
confidence: 99%
“…Thus, the ability to selectively induce acetylation of targeted proteins overcomes many of these challenges. Toward this end, chemical-based approaches have yielded ligand-directed acetyl-donating reagents for stoichiometric, nonenzymatic transfer of acyl groups to lysine residues on specific proteins like androgen receptor, histone H2B, , dihydrofolate reductase, , and phosphoglycerate mutase 1 . Though capable of targeting endogenous POIs, such reagents are “single use”, allowing for the transfer of one acetyl group per molecule and, further, are limited to proteins with available ligands that bind within proximity to targeted recipient lysine residues.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability to selectively induce acetylation of targeted proteins overcomes many of these challenges. Towards this end, ‘all-chemical’ based approaches have yielded ligand-directed acetyl-donating reagents for stoichiometric, non-enzymatic transfer of acyl groups to lysine residues on specific proteins like androgen receptor 48 , histone H2B 4950 , dihydrofolate reductase 5152 , and phosphoglycerate mutase 1 53 . Though capable of targeting endogenous POIs, such reagents are ‘single use,’ allowing for the transfer of one acetyl group per molecule and, further, are limited to proteins with available ligands that bind within proximity to targeted recipient lysine residues.…”
Section: Discussionmentioning
confidence: 99%